On the short-term impact of pollution: The effect of PM 2.5 on emergency room visits - Evangelina Dardati; Ramiro De Elejalde; Eugenio P. Giolito (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2022)
In this paper, we study the short-term effect of fine particulate matter (PM 2.5) exposure on respiratory Emergency Room (ER) visits in Chile, a middle-income country with high levels of air pollution. To instrument for PM 2.5 we use wind speed at different altitudes (pressure levels). Unlike previous papers, our data allow us to study the impact of increasing air pollution at high levels of pollution. We find that a 1 microgram per cubic meter (μg/m3 ) increase in PM 2.5 exposure for one day increases ER visits for respiratory illness by 0.36 percent. The effect is positive for all age groups, including the middle-age population, a novel finding in the literature.
Keywords: I12; I18; Q51; Q53; 330; Air Pollution; PM 2.5; Emergency Room Visits